PENGENDALIAN KUALITAS PRODUK VITABUMIN 130 ML MENGGUNAKAN STATISTICAL QUALITY CONTROL (SQC) DI PT. AKSAMALA ADI ANDANA - Elly Wuryaningtyas Yunitasari; Nina Putri Wardana; Fikri Singgih Wijya (Jurnal Ilmiah Dinamika Teknik, 2021)
PT. Aksamala Adi Andana is a company that produces processed honey products as traditional medicine, especially for children. Based on observations, there were problems with product defects, namely Seal Cap Defects, Folding Defects, and Label Defects. Statistical Quality Control (SQC) used so that there are no defects in products marketed to consumers fulfilled. SQC has quality control tools, namely check sheets, Pareto diagrams, control charts, and cause and effect diagrams. The control chart and Pareto diagram results to determine the proposed improvements to the types of defects that occur most frequently. The results obtained show that there are still out-of-control data on the control chart in the first and second week of June, the third week of July, the first and fourth week of August. There are three most significant defects from the out-of-control data, namely capseal, folding, and label defects. It shows the need to improve the human, material, method, environment, machine, and energy factors using causal diagrams.